1976
DOI: 10.1093/ajcn/29.7.766
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and C levels in infants during the first year of life

Abstract: The considerably lower vitamin E level found in cord blood and in newborns at birth than those found in the venous blood of mothers at delivery are not yet fully explained. In a group of 217 not selected newborns, we attempted to establish the relation between vitamin E and C levels at delivery and the changes during the first year of life. The mean serum vitamin E level rose from 0.37 mg/ml at 3 days to 0.80 mg/100 ml at 6 months and to 0.72 mg/100 ml at 12 months. On the other hand vitamin C mean levels lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Besides CoQ10 ascorbic acid is another important sensitive antioxidant against oxidative stress. Studies concerning age-related plasma levels could demonstrate a significant decrease in ascorbic acid levels in the first year of life in contrast to α-tocopherol [13,44]. This finding might be induced by the poor ascorbic acid content in infant nutrition as discussed by the authors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Besides CoQ10 ascorbic acid is another important sensitive antioxidant against oxidative stress. Studies concerning age-related plasma levels could demonstrate a significant decrease in ascorbic acid levels in the first year of life in contrast to α-tocopherol [13,44]. This finding might be induced by the poor ascorbic acid content in infant nutrition as discussed by the authors.…”
Section: Discussionmentioning
confidence: 91%
“…This finding might be induced by the poor ascorbic acid content in infant nutrition as discussed by the authors. Vobecky and co-workers [44] could demonstrate that dietary histories in infancy show a rather limited choice of vegetables and fruits. Furthermore, most of these products were consumed after cooking [44].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported higher blood vitamin C concentrations at birth in preterm than in term infants, followed by a rapid decline (Gopinathan et al, 1994;Heinonen et al, 1986;Silvers et al, 1998). This decline can be ameliorated by administration of high amounts of vitamin C (Arad et al, 1982;Gopinathan et al, 1994;Heinonen et al, 1986;Silvers et al, 1998;Vobecky et al, 1976). However, the clinical significance of the high plasma levels and the rapid decline is not established.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Distributions of radioactive elements in metals and other materials can be determined by direct contact with an SSNDT [127][128][129][130][131]. Also neutroninduced fission reactions in boron have been used to determine its distribution in steel [132].…”
Section: 4 Use Of Ssnd Ts As Particle Countersmentioning
confidence: 99%